Analysis of sub-synchronous interaction and damping characteristics of weak grid-connected high inertia energy storage synchronous condenser system - Sheng Gong; Jun Yao; Xue Chen; Yuheng Yang; Zhihui Wang (International Journal of Electrical Power & Energy Systems)
Due to the fixed rotor speed and insufficient inertia of conventional DC synchronous condenser (SCs), the high inertia energy storage synchronous condenser (HIESSC) is considered as a promising solution for providing both voltage and frequency support for the grid. However, as a new synchronous condenser, the HIESSC may suffer sub-synchronous oscillations (SSO) because of the interaction between the HIESSC and weak grid. Moreover, there are limited literatures addressing the analysis of internal sub-synchronous interaction within the system. For this issue, the sub-synchronous interaction and damping characteristics of the weak grid-connected HIESSC system are investigated in this article. Firstly, a complete closed-loop transfer function block diagram of the system is developed. Then, in the phase-locked loop (PLL)-dominated SSO mode, the damping paths of the system and dynamic interaction processes in the HIESSC grid-connected system are analyzed. On this basis, the damping contribution of HIESSC and sub-synchronous interaction are evaluated quantitatively by drawing on equivalent damping coefficients in damping torque analysis (DTA). Finally, the effectiveness of the theoretical analysis is validated by simulations and experiments.